Address to the International Labour Conference, June 13, 1997 - Wolfensohn, James D. (World Bank, Washington, DC, 2017)
James D. Wolfensohn, President of the World Bank Group, discusses the relationship, which has been going on for years between the Bank and the International Labour Organization (ILO), has indeed been deepened and strengthened. The Bank has established some work programs, including joint studies on reform of vocational education and training systems, on the labor-market impact of export processing zones, and joint workshops for trade unionists on labor and development issues. Wolfensohn reviewed the differing role of the Bank compared to the ILO. The Bank is focusing direct and specific attention on poverty alleviation within a sustainable environment. He discussed other partners in development: other multilateral institutions, the private sector, civil society, and governments. The aims of the Bank and the ILO are linked to giving individuals a chance for freedom and economic opportunity with a sense of justice and fairness.